THE JUNGLE OF MANAGEMENT THEORY: A JOURNAL REVIEW - Gustiawan, Willson (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2018)
This paper is an article review regarding management theory of Koontz (1980) revisited from his 1960’s first paper. The paper gives a fundamental understanding of the management theory which will be very useful and used during the study period.Through this paper, Koontz examined some approaches to management theory for the last twenty years up to 1980. The management theory jungle that he termed in his 1961 paper are reconsidered. This paper is his report of his revisit to the jungle.As conclusion, there were the need for more effort in disentangling the jungle. The most effective way would be for leading managers to take a more active role in narrowing the widening gap that seem to exist between professional practice and college and university business, management andpublic administration schools.Keywords: management theory, Harold Koontz